Potential spatial intersection between high-seas fisheries and deep-sea mining in international waters. (July 2021) - van der Grient, J.M.A.; Drazen, J.C.
Abstract: Interest in the mining of polymetallic nodules, sulfide deposits, and ferromanganese crusts in the deep sea is growing. While the impacts of deep-sea mining on benthic systems are somewhat understood, there is little information available on pelagic impacts via, for example, the discharge plume. The impacts of these suspended sediments on pelagic communities can have consequences for the fishing industry if their target species are directly or indirectly impacted. Here, we quantify how tuna fisheries on the high seas spatially intersect with mining areas for which exploration contracts have been issued. We explore the spatial intersection of potential mining impacts by investigating different areal extensions around the mining areas as proxies for the spread of potential sediment plumes and movements of tunas. We investigate which countries are fishing in these areas and what percentage of their catches from Regional Fisheries Management Organization (RFMO) areas may intersect with mining activities. We show that for countries that catch the most in mining areas, their catches from mining areas constitute small to moderate parts of their RFMO catches. There are some exceptions amongst these nations and other, often small island nations and/or developing countries, which can derive a high percentage of their RFMO catch from within mining areas, especially if mining plumes spread to a larger extent. RFMOs and other fishery stakeholders should be aware of these potential spatial intersections with their industry and seek to contribute to the development of mining regulations and policies as another stakeholder in the blue economy.